ANALISIS EFEKTIVITAS PEMBELAJARAN JARAK JAUH DI SEKOLAH DASAR - Ika Julianti; Dadang Iskandar; Acep Roni Hamdani; Nurlaila Nurlaila (STKIP Subang, 2022)
The purpose of this research is to describe: 1) The concept of distance learning methods in elementary schools; 2) The application of distance learning in elementary schools so that the learning process is effective; 3) The relationship between distance learning and the effectiveness of the learning process in elementary schools. This research uses descriptive qualitative analysis with the type of literature study or literature study (Library Research), which is a series of activities related to collecting library data by exploring, observing, analyzing, identifying reading journals, notes, reports, research results, and other sources. which is relevant. Sources of data used in this study using primary and secondary data sources. Data collection techniques used in this research are editing, organizing, and finding. And analyzed using comparative, interpretative, deductive and inductive analysis. The results of the analysis that have been carried out prove that distance learning has a fairly good influence on the effectiveness of the learning process in elementary schools. This is proven based on the results of the analysis of research that has been done previously. The implementation of distance learning will be successful or effective if you apply the steps correctly. Distance learning steps include pre-learning steps, during learning and after learning or also called preparation, implementation and evaluation steps.